Analysis Of Consumptive Behavior Factors (Case Study Of Generation Z In Palembang City) - Nuri Annisa Fitri; Hisbullah Basri; Sinta Sinta (UNIVED Press, 2024)
This research aims to find out what factors most influence consumer behavior in generation Z. There are 4 indicators that influence consumer behavior, namely cultural factors, social factors, personal factors and psychological factors. Each of these indicators has sub-indicators, such as Cultural Factors with sub-indicators in the form of culture and sub-culture. Social factors in the form of reference groups, family and role/status. Personal factors in the form of lifestyle and personality. Psychological factors in the form of learning and beliefs. This research uses quantitative methods with survey techniques. The sample in this study was 203 people. The data collection technique uses a questionnaire distributed online via Google Form. The questionnaire consists of 40 statement questions and 2 essay questions. The measurement scale in this study uses a Likert scale. The research instrument will be tested using validity and reality tests via the SPSS application. The results of this research show that the lowest factor is the social factor amounted to 33.28%. Psychological factors amounted to 39.165%, personal factors amounted to 41.4%. Meanwhile, the highest factor is the cultural factor amounted to 41.585%. The results of this study show that cultural factors that most influence the consumer behavior of generation Z.